2015
DOI: 10.5799/jmid.123129
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of clinical and laboratory predictors of fatality in patients with Hantavirus infection

Abstract: Objectives: To determine the clinical and laboratory predictors of fatality among patients with Hantavirus infection. Materials and methods: A retrospective study was conducted on the patients with Hantavirus infection between April 2009and October 2011 at the Black Sea and the Mediterranean regions in Turkey. Demographic, clinical and laboratory findings of fatal cases and non-fatal cases at the admission were compared. Results:Twenty-two patients with confirmed Hantavirus infection were evaluated. Five patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…A murine monoclonal antibody developed for the treatment of HTNV infections was administered as a single-dose intravenous injection to healthy volunteers in a clinical trial, and was shown to be effective against HTNV both in vitro and in vivo [28] . Thus, it is believed that monoclonal antibodies may be a candidate for effective treatment of HFRS [29,30] . Neutralizing antibodies administered early may also play a protective role against the disease [7] .…”
Section: Treatment Antiviral Drugsmentioning
confidence: 99%
See 3 more Smart Citations
“…A murine monoclonal antibody developed for the treatment of HTNV infections was administered as a single-dose intravenous injection to healthy volunteers in a clinical trial, and was shown to be effective against HTNV both in vitro and in vivo [28] . Thus, it is believed that monoclonal antibodies may be a candidate for effective treatment of HFRS [29,30] . Neutralizing antibodies administered early may also play a protective role against the disease [7] .…”
Section: Treatment Antiviral Drugsmentioning
confidence: 99%
“…Early diagnosis, intensive care, and supportive therapy have greatly reduced mortality due to hantavirus infections, with rates of less than 1% for certain subtypes [7,30,31] . Maintaining fluid and electrolyte balance is the key principle of treatment [7] .…”
Section: Supportive Therapymentioning
confidence: 99%
See 2 more Smart Citations
“…Hantaviruses are negative-sense RNA viruses that belong to the Bunyaviridae family [1][2][3]. Epidemiologically HFRS is a rare disease in Albania, but time after time there are cases reported [4].…”
Section: Introductionmentioning
confidence: 99%